Bisphenol A modified DNA: A possible immunogenic stimulus for anti-DNA autoantibodies in systemic lupus erythematosus - Homaidan T. Alhomaidan; Naila Rasheed; Salem Almatrafi; Fahad H. Al-Rashdi; Zafar Rasheed (Taylor & Francis Group, 2019)
Anti-DNA antibodies are now considered as a universal diagnostic feature for the patients with systemic lupus erythematosus (SLE) but the mechanism(s) involved in the generation of these autoantibodies remains to be investigated. Bisphenol A (BPA) is a synthetic phenol extensively used in the manufacturing of polycarbonated plastics. Upon mixing in the diet, it causes several health hazards. This study was undertaken to investigate the contribution of BPA induced DNA damage in SLE patients. Human DNA was modified by BPA in-vitro and the binding characteristics of SLE circulating immunoglobulin Gs (SLE-IgGs) with BPA damaged DNA (BPA-DNA) were screened and compared with the IgGs from normal healthy humans (NH-IgGs). Immunogenicity of BPA-DNA was determined by immunisation in rabbits. DNA from SLE patients (SLE-DNA) or healthy humans (NH-DNA) were isolated and their binding specificity with rabbit anti-BPA-DNA-IgGs was studied. Treatment of human DNA with BPA caused extensive damaged. Circulating SLE-IgGs showed strong recognition of BPA-DNA. BPA-DNA induced high titre antibodies in rabbits. Rabbit anti-BPA-DNA-IgGs showed strong cross reaction with isolated DNA from SLE patients. In short, we concluded that the structural alterations in DNA by BPA, generate neo-epitopes that may be a factor responsible for the induction of anti-DNA autoantibodies in SLE.